185 Howell-Jolly Body-Like Inclusions in Neutrophils of Patients With Myelodysplastic Syndrome: A Novel Correlation. (11th January 2018) - Tong, Yi Tat; Nguyen, Andy; Wahed, Amer
Abstract: Objectives: Howell-Jolly body-like inclusions (HJBLIs) have been classically associated with human immunodeficiency virus (HIV)-infected patients, patients on antiviral medications, and immunosuppressed individuals. These inclusions appear in neutrophils, and unlike Barr bodies, are completely detached inclusions in the cytoplasm. They are thought to represent detached nuclear fragments produced from dysplastic granulopoiesis. To the best of our knowledge, no association of HJBLIs and myelodysplastic syndrome (MDS) has been reported previously. Here we establish an unprecedented correlation of HJBLIs in patients with, MDS. Interestingly, in all 11 cases, none of the patients has a history of HIV or was on immunosuppressants and antiviral medications. Methods: A total of 11 bone marrow cases from patients diagnosed with, MDS, , MDS/myeloproliferative neoplasm (MPN), and acute myeloid leukemia (AML) with, MDS-related changes were studied. Detailed medical records review was performed to ensure none of the 11 patients had a history of HIV or was on immunosuppressants and antiviral medications. Peripheral blood and bone marrow aspirate smears were reviewed. Results: Seven out of 11 (64%) cases show detached intracytoplasmic inclusions in mature neutrophils consistent with HJBLIs. They were also seen in myelocytes in one of the 11 cases. Conclusion: In review of literatures, HJBLIs seem to correlate with immunosuppression and antiviral therapies with nucleoside analogs. The morphology of HJBLIs can be easily confused with other intracytoplasmic inclusions, such as large leukocyte granules found in Chédiak-Higashi syndrome. We propose that the formation of HJBLIs is the consequence of dysplasia and hence its correlation with, MDS. The inclusions are, however, seen in only a minority of white cells (<1%), which is probably why they were not brought to practicing pathologists' awareness in the past. The findings from this study would contribute important data to more future scientific research to determine the exact mechanism of HJBLI formation.